Effects of nanoclay on physical and dimensional stability of bamboo/kenaf/nanoclay reinforced epoxy hybrid nanocomposites - Siew, Sand Chee; Jawaid, Mohammad; Hameed Sultan, Mohamed Thariq; Alotmane, Othman Y.; Abdullah, Luqman Chuah (Elsevier, 2020)
The objective of current work is to evaluate the density, void content, water absorption, thickness swelling and thermal expansion of non-woven bamboo mat (B)/ woven kenaf mat (K)/nanoclay/epoxy hybrid nanocomposites. The natural fibers based hybrid nanocomposites were prepared by incorporation of montmorillonite (MMT), halloysite nanotube (HNT) and organically modified montmorillonite (OMMT) at 1 wt.% loading, through hand lay-up technique. Water absorption was investigated by soaking the samples with distilled water at room temperature until saturation point and the thickness swelling was also measured as per standard. Thermomechanical analyser (TMA) was used to study the dimensional stability caused by temperature variation. Addition of nanoclay increase the density, reduced the void content and suppress water uptake in all hybrid nanocomposites. B/K/OMMT hybrid nanocomposites exhibit better dimensional stability with regards to water absorptions and thermal expansion as compare to B/K/MMT and B/K/HNT. The improvement can be attributed by the uniformly dispersed and strong interfacial adhesion bonding between the OMMT and epoxy matrix. The develop nanocomposites in this work can be utilized for building and automotive application which required high dimensional stability property.